(untitled) (مجلة البحوث الأكاديمية, 2025)
Sperm preservation is vital for the success of assisted reproductive techniques (ART). Laboratory stress can compromise sperm structure and function, leading to oxidative damage to proteins, lipids, and nucleic acids, which impairs fertilization. Recently, plant extracts have emerged as a cost-effective, natural method to enhance semen quality during storage. Linseed, rich in phenolic compounds, polyunsaturated fatty acids (70%, mainly alpha-linoleic and linoleic acids), and vitamin E, serves as an antioxidant. This study aimed to assess the impact of different concentrations of flaxseed extract on human sperm parameters during storage. Semen samples with normal parameters were collected from healthy participants and treated with varying concentrations (0%, 100 µg/ml, and 200 µg/ml) of flaxseed extract while stored at 37°C for 0, 6, and 10 hours. Improvements in sperm parameters were recorded and compared to control groups. Treatment groups exhibited increased total motility (LIN, STR, and progressive movement) compared to controls (p < 0.05), particularly at higher concentrations. Linseed extract also significantly reduced sperm mortality compared to controls (p < 0.05), especially at lower concentrations. This study demonstrates that antioxidant-rich plant extracts like flaxseed can enhance semen quality during storage by improving sperm motility and reducing oxidative stress.